2011
DOI: 10.1530/erc-10-0257
|View full text |Cite
|
Sign up to set email alerts
|

MiR-129-5p is required for histone deacetylase inhibitor-induced cell death in thyroid cancer cells

Abstract: The molecular mechanism responsible for the antitumor activity of histone deacetylase inhibitors (HDACi) remains elusive. As HDACi have been described to alter miRNA expression, the aim of this study was to characterize HDACi-induced miRNAs and to determine their functional importance in the induction of cell death alone or in combination with other cancer drugs. Two HDACi, trichostatin A and vorinostat, induced miR-129-5p overexpression, histone acetylation and cell death in BCPAP, TPC-1, 8505C, and CAL62 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 29 publications
(41 reference statements)
2
51
0
Order By: Relevance
“…Interestingly a histone deacetylase inhibitor that has been shown to increase frataxin levels (Herman et al, 2006) caused decrease in the miR-886-3p levels. Histone deacetylase inhibitors have been shown previously to alter miRNA levels (Scott et al, 2006;Brest et al, 2011); however, this is the first link between HDAC inhibition and suppression of levels of miR-886-3p leading to enhanced frataxin expression (Fig. 3).…”
Section: Discussionmentioning
confidence: 89%
“…Interestingly a histone deacetylase inhibitor that has been shown to increase frataxin levels (Herman et al, 2006) caused decrease in the miR-886-3p levels. Histone deacetylase inhibitors have been shown previously to alter miRNA levels (Scott et al, 2006;Brest et al, 2011); however, this is the first link between HDAC inhibition and suppression of levels of miR-886-3p leading to enhanced frataxin expression (Fig. 3).…”
Section: Discussionmentioning
confidence: 89%
“…For example, it has been demonstrated that miR-129-5p is required for histone deacetylase inhibitorinduced cell death in thyroid cancer cells [194]. Liu et al found that miR-129-5p suppressed tumor growth and reduced cell migration through inhibition of VCP (Valosin containing protein) in hepatocellular carcinoma [195].…”
Section: Regulation Of Fbw7 By Mir-129-5pmentioning
confidence: 99%
“…Histone deacetylation allows DNA to wrap more tightly, thus becoming less accessible to the cell's transcription machine (1,7). More specifically, HDACs suppress the expression of tumor-suppressor genes and promote, in this way, the development and progression of tumors (13). In addition, HDAC activity is enhanced in both malignant and benign neoplasms (7).…”
mentioning
confidence: 99%
“…What is more, they can sensitize tumor cells to radiation and chemotherapy (7) and make tumors more amenable to surgery (13). More specifically, HDACIs have been shown to synergize with antitumor/chemotherapy drugs, such as paclitaxel, cisplatin, etoposide, doxorubicin, the HAMLET protein complex, etc.…”
mentioning
confidence: 99%
See 1 more Smart Citation